2019
DOI: 10.35940/ijrte.d9016.118419
|View full text |Cite
|
Sign up to set email alerts
|

System Design of Augmented Reality Technology to Strengthen Sustainable Imaging of Kujang Products Based on Local Culture

Eneng Tita Tosida*,
Deden Ardiansyah,
Agung Djati Walujo
et al.

Abstract: Kujang products, which are reproduced by a number of micro businesses in West Java, have not been able to increase public interest in preserving them as high value tourism products. Kujang's image as a "valuable" local culture-based product in the community is still low. This results in a still low level of quantity and quality of tourism based on local culture, especially those related to Kujang. Although the government has launched a work program to achieve the target for the next five years.. One way that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Waxing activity was embedded in the software for the older age group. AR architecture has been developed to aid in the understanding of local batik knowledge and philosophy for elementary (Tosida et al, 2018), vocational (Widiaty et al, 2015), and special need students (Widiaty et al, 2017). Tosida et al’s (2018) study showed that AR technology can be used to increase student learning interest.…”
Section: Batik As An Ichmentioning
confidence: 99%
See 1 more Smart Citation
“…Waxing activity was embedded in the software for the older age group. AR architecture has been developed to aid in the understanding of local batik knowledge and philosophy for elementary (Tosida et al, 2018), vocational (Widiaty et al, 2015), and special need students (Widiaty et al, 2017). Tosida et al’s (2018) study showed that AR technology can be used to increase student learning interest.…”
Section: Batik As An Ichmentioning
confidence: 99%
“…AR architecture has been developed to aid in the understanding of local batik knowledge and philosophy for elementary (Tosida et al, 2018), vocational (Widiaty et al, 2015), and special need students (Widiaty et al, 2017). Tosida et al’s (2018) study showed that AR technology can be used to increase student learning interest. Widiaty et al’s (2017) assessment of AR for batik patterns developed for android mobile resulted in an increase in spatial intelligence and enthusiasm among special needs children.…”
Section: Batik As An Ichmentioning
confidence: 99%
“…Bogor's new normal batik village is a village formed by a service team as a form of service to the people of Tegal Village (Tosida et al, 2019), (Fauzi & Defianisa, 2019). This is because with this socialization, it is expected that there will be active participation from the entire community of Tegal Village, especially the participation of PKK women or youth organizations or non-productive communities who have previously been appointed to the Batik Micro Business Group through the Decree of the Tegal Village Head who will be trained in batik making.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem faced by tourism in Ciasmara village is the limited promotional infrastructure. Unavailability of an easily accessible large car park location makes this location difficult to reach by tourism cars and buses (Tosida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of information and communication technology is expected to overcome obstacles related to space and distance. Through information and communication technology, obstacles such as knowledge sharing between fellow citizens and policy holders can be overcome, besides that through information and communication technology, it is also expected to increase the capacity of Ciasmara villagers to manage tourism in the village (Tosida et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%